2005
DOI: 10.2134/agronj2005.0399
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Evaluation of Poultry Litter as a Source of Nitrogen for Cotton and Corn

Abstract: Although cotton is the number one row crop in Alabama, Georgia, Mississippi, and Arkansas in terms of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
68
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 19 publications
16
68
2
1
Order By: Relevance
“…The treatment with chemical fertilization also produced taller plants than those of the treatment with 14,860 kg ha -1 of poultry litter. Mitchell & Tu (2005), when comparing the same nitrogen level using ammonium nitrate and poultry litter, observed that cotton plants fertilized with chemical fertilizer showed higher height than the plants fertilized with poultry litter, results similar to those found in the present study.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…The treatment with chemical fertilization also produced taller plants than those of the treatment with 14,860 kg ha -1 of poultry litter. Mitchell & Tu (2005), when comparing the same nitrogen level using ammonium nitrate and poultry litter, observed that cotton plants fertilized with chemical fertilizer showed higher height than the plants fertilized with poultry litter, results similar to those found in the present study.…”
Section: Resultssupporting
confidence: 91%
“…Mitchell & Tu (2005), while evaluating the influence of poultry litter levels on cotton, found that plants treated with litter were taller. Besides plant height, a quadratic effect of the stem diameter in response to increasing poultry litter levels was also observed (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations